Видатні діячі кирило-мефодіївського братства - Ганзя, Р. С. (ХНУРЕ, 2023)
Ukrainian history includes man y outstanding cultural figures. The study was conducted on the example of personalities of the national revival. Members of the Kyrillo-Methodiian Brotherhood developed culture together. Namely, they were engaged in the publishing of Ukrainian periodicals and the development of education. They also worked separately, each in their own field: literature, painting, art, etc. The work compares past and present cultural activities. This is relevant, because cultural figures had to work in conditions of an unstable situation in the country and protect its interests.